PROTECTIVE EFFECT OF VITAMIN C ON MONOSODIUM GLUTAMATE INDUCED CHANGES IN THE OVIDUCT OF RATS - Abbasi, Sumaira; Khattak, Saima Mumtaz; Malik, Sana (Journal of Ayub Medical College Abbottabad, 2018)
Background: This study was conducted to evaluate the effect of Vitamin C on Monosodium Glutamate induced histopathological changes in oviduct of adult female Sprague Dawley rats. The duration of study was 6 months. It was an analytical experimental randomized control trial. Methods: In this experimental study, 45 female adult Sprague Dawley rats of 10-14 weeks were used and divided into 3 groups. Each group contains 15 rats. Control group (C) received standard laboratory diet. Experimental group A, was given Monosodium Glutamate (0.08 mg/kg body weight/ day) whereas experimental group B, was served on both MSG and Vitamin C (250 mg/kg body weight/day). All groups received diet for a period of 4 weeks. After 4 weeks all rats were sacrificed and oviducts were obtained. For the study of tissue under light microscopy, tissue processing was done by using Haematoxylin and Eosin stain and 5micrometer thick sections were taken from the ampullary part of oviduct. Results: After administration of MSG, group A showed vacuolization of epithelial cells, infiltration of RBCs in lumen with substantial decrease in the diameter of oviduct in group A. Protective effects were seen in vitamin C supplemented group B, with decrease in epithelial vacuolization and RBCs infiltrate along with increase in diameter of oviduct. Conclusion: Vitamin C has protective effect on Monosodium Glutamate induced histological changes in oviduct of rats. Keywords: diameter of oviduct; MSG; RBC; Vitamin C; Vacuolization